Identifikasi Unsur Hara Sulfur pada Sistem Irigasi Primer di Tanah Sawah Wilayah Bendungan Arca Kiri, Kabupaten Banyumas - Agustine, Leony; Wibowo, Amanullah Thaariqa Tri; Begananda, Begananda (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2021)
This study aims to determine 1) the amount of nutrient content of Sulphur in a paddy field in the irrigation channel of Arca Kirit dam in Banyumas Regency, 2) nutrient distribution of Sulphur in paddy field in the irrigation channel of Arca Kiri dam in Banyumas Regency, and 3) recommendations of Sulphur fertilizers in paddy field in the irrigation channel of Arca Kiri dam in Banyumas Regency . The research was conducted in paddy field, in the irrigation channel of Arca Kiri dam in Banyumas Regency, then continued with analysis of the soil in the Institute of Determining Technology of Agriculture (BPTP), Yogyakarta . The research carried out by the determination of sample points based on a purposive random sampling be based Land Homogenous Unit (SLH). Land Homogenous Unit arranged by overlaying the Administrative Map, Slope Map, and Soil Type Map. The number of samples is 8, which is located in 5 villages. The variables were observed namely the nutrient content of Sulphur, EC, pH (H2O), and BS of land. The results showed that the nutrient content of Sulphur from both SLH relatively high, there were SLH A1 reach 86.20 ppm and SLH A2 reach 85.33 ppm. Sulphur fertilizer recommendations for SLH A1 is 10.64 kg S/ha and SLH A2 is 14.60 kg S/ha .